Market Entries and Exits and the Nonlinear Behaviour of the Exchange Rate Pass-Through into Import Prices - Nils Herger (Swiss National Bank, Study Center Gerzensee, 2013)
This paper develops an empirical framework giving rise to a nonlinear behaviour of the exchange rate pass-through (ERPT). Rather than shifts between low and high inflation, the nonlinearity arises when large swings in the exchange rate trigger market entries and exits of importing firms. Switching regressions are used to distinguish between low and high pass-through regimes of the exchange rate into import prices. For the case of Switzerland, the corresponding results suggest that, though inflation has been low and stable, the ERPT still doubles in value in times of a rapid appreciation of the Swiss Franc.
Keywords: F15; F31; L11; 330; Exchange Rate Pass-Through; Import prices; Switching regression